Intracoronary allogeneic cardiosphere‐derived stem cells are safe for use in dogs with dilated cardiomyopathy. Issue 8 (15th March 2017) - Hensley, Michael Taylor; Tang, Junnan; Woodruff, Kathleen; Defrancesco, Teresa; Tou, Sandra; Williams, Christina M.; Breen, Mathew; Meurs, Kathryn; Keene, Bruce; Cheng, Ke
Abstract: Cardiosphere‐derived cells (CDCs) have been shown to reduce scar size and increase viable myocardium in human patients with mild/moderate myocardial infarction. Studies in rodent models suggest that CDC therapy may confer therapeutic benefits in patients with non‐ischaemic dilated cardiomyopathy (DCM). We sought to determine the safety and efficacy of allogeneic CDC in a large animal (canine) model of spontaneous DCM. Canine CDCs (cCDCs) were grown from a donor dog heart. Similar to human CDCs, cCDCs express CD105 and are slightly positive for c‐kit and CD90. Thirty million of allogeneic cCDCs was infused into the coronary vessels of Doberman pinscher dogs with spontaneous DCM. Adverse events were closely monitored, and cardiac functions were measured by echocardiography. No adverse events occurred during and after cell infusion. Histology on dog hearts (after natural death) revealed no sign of immune rejection from the transplanted cells.